A slab break-off model for mafic–ultramafic igneous complexes in the East Kunlun Orogenic Belt, northern Tibet: insights from early Palaeozoic accretion related to post-collisional magmatism. Issue 10 (3rd July 2019) - Yan, Jia-ming; Sun, Feng-yue; Li, Liang; Yang, Yan-qian; Zhang, De-xin
ABSTRACT: The East Kunlun Orogenic Belt (EKOB) in northern Tibet provides an important record of the amalgamation of the Wanbaogou oceanic basalt plateau and the Qaidam Block. Here we report geochemical, geochronological, and Hf isotopic data for newly identified late Silurian–Early Devonian mafic–ultramafic igneous complexes from the EKOB at the northern margin of the Tibetan Plateau. These complexes are dominantly composed of gabbro and pyroxenite rocks. Three complexes yield zircon U–Pb ages of 398.8 ± 1.8, 420.2 ± 1.2, and 413.4 ± 0.78 Ma. The εHf (t) values of zircons range from +0.8 to +3.3 with TDM1 ages of 897 to 998 Ma. Modelling of the geochemical data indicates that these igneous complexes have a hybrid origin, involving depleted mantle fluids derived from a previous subduction event and crustal materials. The geochemical and geochronological data suggest that these complexes formed in a post-collisional setting linked to break-off of a subducted oceanic slab, which occurred after the Wanbaogou oceanic basalt plateau amalgamated with the Qaidam Block in the late Silurian–Early Devonian.